FACTORS RELATED TO ANTENATAL CARE VISITS FOR PREGNANT WOMEN IN THE WORKING AREA OF THE BATUNADUA PUSKESMAS - siregar, Nurelilasari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
Incomplete pregnancy checks can indirectly affect pregnancy complications in the mother that are not detected and can cause the risk of maternal death. The World Health Organization recommends that six visits during pregnancy be mandatory during pregnancy at predetermined standards and times. The purpose of this researched wasto knowrelated factors with antenatal care visits to pregnant women in the Batunadua Working Area. The type of researched was quantitative research with a cross sectional study approach design. The population in this study was all 49 third trimester pregnant women, the sampling technique used total sampling. The analysis used is the Chi Square test. The results of this study showthat employment status (0.003), knowledge (0.000),and attitude (0.000) relatedwith antenatal care visits in pregnant women. Conclusion reached job status, knowledge and attitude related to antenatal care visits in pregnant women. It is hoped that health workers will be more comprehensive in providing counseling regarding antenatal care visits to pregnant women.